Rola funduszy strukturalnych w rewitalizacji regionów charakteryzujących się dużą koncentracją schyłkowych gałęzi przemysłu - Taraszkiewicz, Jolanta (The Importance of the Structural Funds in Revitalization Regions with High Concentration of Phase Down Industries, 2006)
The paper examines the role of structural funds in supporting structural adjustment in regions with high concentration of traditional sectors of industry. The analysis of programmes' priorities of objectives 1 and 2 indicates that these regions still receive significant help in the framework of regional policy. Moreover the analysis indicates increasing role of horizontal undertakings which focus on establishing environment for business, supporting SME and economic diversification of regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 411-420